PENGARUH LAMA PEMANASAN BASAH DAN PERENDAMAN DALAM GIBERELIN TERHADAP PEMATAHAN DORMANSI BENIH KELAPA SAWIT (Elaeis guineensis jacq.) - Agustiansyah, Agustiansyah; Ardian, Ardian; Setiawan, Kukuh; Dewi, Erni Permata (Agrin, 2020)
The aims of   this research to determined the effect wet heating and  immersion in gibberellins on breaking dormancy of  oil palm seed. The treatment was arranged in  factorially with two factors in the Completely Randomized Design. The first factors was wet heating which consists of five levels, (1) 20 days of heating; (2) 25 days of heating (3) 30days of heating (4) 35 days of heating (5) 40 days of heating.  The second factor was the concentrations of gibberellin in four levels,  (1) 0 ppm; (2) 100 ppm; (3) 200 ppm and (4) 300 ppm.  Based on the results  could be concluded that (1) wet heating could increased the percentage of germination, maximum growth potential, speed of germination, and time of emergence of sprouts, (2) 30 days wet heating treatment + immersion in 200 ppm giberelin was the best treatment in percentage of germination (64 % ± 1.3), maximum growth potential(70.7%±1.4), and speed of germination  (29% ± 1.0 per etmal).